2020
DOI: 10.1016/j.psj.2019.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Comparative aspects of phytase and xylanase effects on performance, mineral digestibility, and ileal phytate degradation in broilers and turkeys

Abstract: Two experiments were performed, using broilers or turkeys, each utilizing a 3 × 2 factorial arrangement, to compare their response to phytase and xylanase supplementation with growth performance, nutrient digestibility, and ileal phytate degradation as response criteria. For both experiments, 960 Ross 308 or 960 BUT 10 (0-day-old) birds were allocated to 6 treatments: (1) control diet, containing phytase at 500 FTU/kg; (2) the control diet with xylanase (16,000 BXU/kg); (3) the control diet supplemented on top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
(30 reference statements)
4
14
2
Order By: Relevance
“…Although in the current study, the increase in Bifidobacterium proportions were not linked to higher concentrations of SCFA measured, other studies have demonstrated that XOS selectively increases the abundance of Bifidobacterium and the production of butyrate and acetate ( Van Craeyveld et al., 2008 ). In any case, in this study, xylanase supplementation improved feed conversion ratio in broilers and turkeys ( Olukosi et al., 2020 ), suggesting a possible link between this bacterial group and performance.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Although in the current study, the increase in Bifidobacterium proportions were not linked to higher concentrations of SCFA measured, other studies have demonstrated that XOS selectively increases the abundance of Bifidobacterium and the production of butyrate and acetate ( Van Craeyveld et al., 2008 ). In any case, in this study, xylanase supplementation improved feed conversion ratio in broilers and turkeys ( Olukosi et al., 2020 ), suggesting a possible link between this bacterial group and performance.…”
Section: Discussionmentioning
confidence: 48%
“…All growth performance, ileal digestibility, and digesta inositol phosphate concentration results from the experiments are presented in ( Olukosi et al., 2020 ). The nutrient profile in the diets ( Table 2 ) and the xylanase activities ( Table 3 ) were met, but the analyzed phytase in the diets were greater than expected ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The difficulties in degrading lower phytate esters may also be influenced by an interactive effect of phytase dose and age of broilers ( Olukosi et al., 2020 ). In research presented herein, concentrations of IP3 and IP4 in the ileal digesta increased as phytase dose is increased from 0 to 1,500 FTU/kg but decreased when phytase is further increased to 40,500 FTU/kg.…”
Section: Discussionmentioning
confidence: 99%